ANALISIS PERBANDINGAN SIKAP KONSUMEN TERHADAP ATRIBUT PRODUK KOPI GOOD DAY DAN LUWAK WHITE COFFEE DI KOTA PEKANBARU - Halim M Aulia; Restut Sri; Nursanti Aida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This Study aime to compare the the consumer attitude toward product attributesof kopi Good Day and Luwak White Coffee Ready to Drink in Pekanbaru city.This research sample is the society of Pekanbaru city was consumed one coffeebrand between of kopi Good Day and Luwak White Coffee was randomly selected.Data analysis using descriptive analysis with quantitative analysis, multiattributesmodel Fishbein, Mann Whitney test using SPSS (Statistical Package For theSocial Sciences) version 20.00. The result showed that overall consumer has agood attitude on product attributes toward kopi Good Day and Luwak WhiteCoffee. Score of taste variance attribute of kopi Good Day is better than LuwakWhite Coffee, while the score of expired date attributes of Luwak White Coffee isbetter than kopi Good Day. Overall points score of attributes product of GoodDay is higher than Luwak White Coffee. Keyword : Product Attributes, Consumer Attitude